THE INFLUENCE OF ADMINISTRATIVE SERVICES, MEDICAL SERVICES AND DRUG AVAILABILITY ON PATIENT SATISFACTION AT PUSKESMAS WAISAI RAJA AMPAT, MODERATED BY PERCEIVED SERVICE QUALITY: - Lolinia Agustina Florensia; Hery Winoto Tj; Fushen (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of administrative services, medical services, and drug availability on patient satisfaction, as well as the moderating role of service quality perception in these relationships. The research employs a quantitative approach with a descriptive method. The results indicate that administrative services, medical services, and drug availability significantly affect patient satisfaction. Furthermore, service quality perception strengthens the relationship between administrative services, medical services, and drug availability with patient satisfaction. These findings emphasize the importance of improving healthcare service quality to optimize patient satisfaction.